2015
DOI: 10.1186/s12955-015-0229-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and the predictive role of sense of coherence, spirituality and religious coping in a sample of Iranian women with breast cancer: a prospective study with comparative design

Abstract: BackgroundThere is disagreement among studies of health-related quality of life (HRQoL) changes in breast cancer patients over time. Reportedly, assessment of HRQoL prior to diagnosis may be crucial to provide a clear point of comparison for later measurements. The aims of this study were (1) to investigate changes in HRQoL, sense of coherence (SOC), spirituality and religious coping in a group of women with breast cancer from the pre-diagnosis phase to 6 months later in comparison with a control group, and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 74 publications
5
91
1
3
Order By: Relevance
“…Regarding education level, 3 studies found that higher education level predicted better quality of life and fewer depressive symptoms . Nine studies found no association .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding education level, 3 studies found that higher education level predicted better quality of life and fewer depressive symptoms . Nine studies found no association .…”
Section: Resultsmentioning
confidence: 96%
“…Three studies found that advanced cancer stage predicted poorer quality of life, but 2 studies found no associations . Two studies examined the association between the number of lymph nodes affected and psychological adjustment.…”
Section: Resultsmentioning
confidence: 99%
“…The growing literature showed mixed results on the association between religious coping and cancer distress (Trevino et al 2014;Rohani et al 2015;Zamanian et al 2015). In a systematic review of 17 studies examining religious/spiritual coping strategies in cancer adjustment, Thuné-Boyle et al (2006) found seven of the studies showed some evidence for the beneficial effect of religious coping, with one study showing religious coping to be detrimental in a subgroup of their population.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, approximately six million people have SSIO insurance in Tehran city [12,13]. Evidence has been published regarding the HRQoL of patients with many diseases and chronic conditions in Iran [14,15]. Nonetheless, insufficient evidence-based information regarding HRQoL and its determinants within the essential health and health-related insurance system in Tehran and throughout Iran has been published.…”
Section: Introductionmentioning
confidence: 99%